Evolution of phage display libraries for therapeutic antibody discovery - Yang Zhang (mAbs)
Monoclonal antibodies (mAbs) and their derivatives have emerged as one of the most important classes of biotherapeutics in recent decades. The success of mAb is due to their high versatility, high target specificity, excellent clinical safety profile, and efficacy. Antibody discovery, the most upstream stage of the antibody development pipeline, plays a pivotal role in determination of the clinical outcome of an mAb product. Phage display technology, originally developed for peptide directed evolution, has been extensively applied to discovery of fully human antibodies due to its unprecedented advantages. The value of phage display technology has been proven by a number of approved mAbs, including several top-selling mAb drugs, derived from the technology. Since antibody phage display was first established over 30 years ago, phage display platforms have been developed to generate mAbs targeting difficult-to-target antigens and tackle the drawbacks present in in vivo antibody discovery approaches. More recently, the new generation of phage display libraries have been optimized for discovery of mAbs with ”drug-like” properties. This review will summarize the principles of antibody phage display and design of three generations of antibody phage display libraries.